The relationship of the decision to the level of technical performance in volleyball among third-grade students in the College of Education and Sport Sciences / University of Baghdad - SHIHAB, AMMAR MUAYED; SHIHAB, AMMAR MUAYED (International Journal of Psychosocial Rehabilitation, 2020)
The decision-making process in the life of the learner is a prerequisite, many of the positions faced in practical lessons, are essentially situations that require decisions, and the importance of research is to identify the relationship between the speed of decision-making and the level of technical performance in volleyball students third grade During the researcher and his interest in the game of volleyball found that there is difficulty in the performance of skills and decision-making while playing in volleyball at more, therefore, the researcher to study the relationship between decision-making level of technical performance in volleyball for third grade students in the Faculty of Physical Education and The purpose of the research was to identify the decision making among the third grade students in the College of Physical Education and Sports Science / University of Baghdad, and to identify the relationship between decision-making and the level of technical performance in volleyball for the research sample, the descriptive method was used in the relationship method A sample of the third grade students in the College of Physical Education and Sport Sciences University of Baghdad and the number of(127) students and by lot was selected two sections (L) to represent the sample of the research (30) students, (24%) From the community of origin, the student scores on the exam a For the quarterly level of technical performance to determine the level of skill performance as well as the application of decision-making scale and after data collection and processing statistically concluded that the research sample has a good level of decision-making during play, and a positive relationship between the level of technical performance of students and decision-making them, previous experience in skills play a positive role In decision-making.